Responses of metastatic primary fallopian tube carcinoma to pembrolizumab and nab-paclitaxel: A case report - Jiang, Jian (Medicine (Baltimore), 2020)
RATIONALE: Primary fallopian tube carcinoma (PFTC) is an extremely rare but invasive malignancy with a dismal prognosis. Very few data exist on the salvage treatment for patients with PFTC. Here we report a case showing an impressive response to immunotherapy combined with chemotherapy, which have never been reported before on patients with metastatic PFTC. PATIENT CONCERNS: A 42-year-old woman, who was diagnosed with PFTC in 2010, had been failed of multiple systemic therapies and antiangiogenic therapy because of the disease recurrence and progression. DIAGNOSIS: Metastatic primary fallopian tube carcinoma. INTERVENTIONS: The patient underwent surgery in May 2010 and had multi-line chemotherapies plus an anti-vascular endothelial growth factor (anti-VEGF) monoclonal antibody for about 9 years. Due to treatment failure the patient accepted the immunotherapy with the checkpoint inhibitor, pembrolizumab, combined with nab-paclitaxel from December 2018 to April 2019. OUTCOMES: The patient showed a complete response after 6 cycles(,) treatment. Thus far, the patient is taking pembrolizumab as maintenance and remains in good health. LESSONS: Pembrolizumab combined with chemotherapy for treatment of PFTC may provide a positive antitumor effect in multiple metastatic lesions, but more clinical evidence is needed to confirm the efficacy and safety.